2021
DOI: 10.3390/v13112212
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNAseq Profiling of Human γδ T Lymphocytes in Virus-Related Cancers and COVID-19 Disease

Abstract: The detailed characterization of human γδ T lymphocyte differentiation at the single-cell transcriptomic (scRNAseq) level in tumors and patients with coronavirus disease 2019 (COVID-19) requires both a reference differentiation trajectory of γδ T cells and a robust mapping method for additional γδ T lymphocytes. Here, we incepted such a method to characterize thousands of γδ T lymphocytes from (n = 95) patients with cancer or adult and pediatric COVID-19 disease. We found that cancer patients with human papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
(78 reference statements)
0
22
0
Order By: Relevance
“…Interestingly, the authors demonstrated that γδ T cells (Vγ9 and non-Vγ9) of severe COVID-19 adult patients are recruited in the lesions of the lung from peripheral blood and showed an effector/exhausted phenotype. In addition, in pediatric acute COVID-19 patients, the authors observed a γδ T-cell lymphopenia similar to the adult patients [55].…”
Section: Severe Acutementioning
confidence: 77%
“…Interestingly, the authors demonstrated that γδ T cells (Vγ9 and non-Vγ9) of severe COVID-19 adult patients are recruited in the lesions of the lung from peripheral blood and showed an effector/exhausted phenotype. In addition, in pediatric acute COVID-19 patients, the authors observed a γδ T-cell lymphopenia similar to the adult patients [55].…”
Section: Severe Acutementioning
confidence: 77%
“…This trajectory also constitutes a reference roadmap onto which ab extra γδ T cells from any additional scRNAseq datasets can now be positioned such as to identify their hallmarks. The γδ T cells infiltrating human tumors, and those from blood or lung lesions of COVID-19 patients were characterized accordingly [3]. Likewise, mapping of γδ T cells extracted from a human γδ T cell lymphoma scRNAseq dataset had never been attempted, however, and the present study reports its successful use for characterizing CTCL of γδ T lineage.…”
Section: Discussionmentioning
confidence: 99%
“…We further refined the transcriptomic transitions underlying this differentiation by delineating 14 successive milestones from the Tn to Temra cells as visualized in a pseudotime-based trajectory [2]. The differentiation stages of γδ T lymphocytes in patients with cancers or with coronavirus disease 2019 (COVID-19) were characterized accordingly and unveiled the association of circulating γδ T lymphocytes with the viral status of individuals [3]. These studies illustrated the power and resolution achieved by trajectory mapping for normal γδ T lymphocytes, but its potential for characterizing the differentiation of malignant γδ T cells was unknown.…”
Section: Introductionmentioning
confidence: 99%
“…233 This subset may also form a part of the immune response to SARS-CoV-2, localizing to the lung from peripheral blood and persist as tissue-resident memory-like cells. 234 However, a study has shown that γδ T cell populations decrease during SARS-CoV-2 infection, possibly a result of exhaustion. 235 However, most studies outline a transitional role for γδ T cell subsets as they aid in implantation via inflammation and must quickly…”
Section: Roleofγδtcellsinviralrespiratoryinfectionsmentioning
confidence: 99%
“…Earlier work with SARS‐CoV‐1 identified that IFN‐γ+ Vγ9Vδ2 T cells were an important portion of the effector memory T cell response to SARS‐CoV‐1 233 . This subset may also form a part of the immune response to SARS‐CoV‐2, localizing to the lung from peripheral blood and persist as tissue‐resident memory‐like cells 234 . However, a study has shown that γδ T cell populations decrease during SARS‐CoV‐2 infection, possibly a result of exhaustion 235 …”
Section: γδ T Cellsmentioning
confidence: 99%